Higher Consumption of Carbonated Drinks and Fast Food Related to Depression and Quality of Life in Adolescent Girls - Abbas Ali Sangouni; Zahra Darabi; Majid Ghayour-Mobarhan; Sayyed Saeid Khayyatzadeh (Journal of Nutrition and Food Security)
Background: The association between fast food, whole grain, refined grain and carbonated drink consumption and depression and quality of life (QoL) was evaluated in Iranian adolescent girls. Methods: In this cross-sectional study, 733 adolescent girls were included from Mashhad and Sabzevar cities in northeastern Iran. The Beck Depression Inventory (BDI) and SF-12v2 questionnaire were used to assess depression and QoL, respectively. A valid and reliable food frequency questionnaire was used to obtain dietary intakes of the study participants. To explore the association between intake of food groups and depression and QoL. It was used linear and logistic regression in crude and adjusted models. Results: There was a signiﬁcant decreasing trend in the odds of poor QOL and depression across increasing quartile intake of whole grain; but, there was no linear relationship between whole grain intake and depression and QoL score. In addition, participants in the highest quartile of carbonated drink consumption had higher odds of poor QoL compared to the first quartile (OR: 1.33; 95% CI: 1.00–2.32, P=0.04). A positive association was found between intake of fast food and depression score (β=0.09). Intake of fast food was inversely associated with QoL score (β=-0.081). However, there was no significant relationship between intake of refined grains and carbonated drinks and depression, and between whole grain and refined grain intake and QoL. Conclusions: The results demonstrated an inverse association between fast food intake and depression and QOL. To better conclude, further studies evaluating the association of various food groups with depression and QoL.